Production system of apartment house as an enterprise - Shcherbyna , A. (Ways to Improve Construction Efficiency, 2021)
The specific problems of apartment building management in Ukraine, which arose as a result of housing privatization using the approaches of civil rather than commercial law, are considered. The recognition of the apartment as real estate, the organization of house management through the voluntary creation of condominiums in the form of a public organization; absence of land and house as real estate in the account of the subject of ownership and management are criticized. The analysis of the literature showed the need for a profound rethinking of ways to improve home management. The purpose of the article is to consider an apartment building as a primary object of ownership and as a production system, an economic and not public organization, enterprise. The methodological approach in substantiating the ways to solve the problem and in formulating conclusions is to compare these alternatives of joint ownership with the use of the provisions of system analysis, models and organizational and legal forms of enterprises. It is shown that in the housing sector as a production subsystem of the sphere of social production, and in it - in the multi-apartment housing stock as a subsystem, the house is their element. Home management is mostly organized by apartment owners as a joint household or condominium. However, a modern apartment building in a business environment is a complex production system that has all the functional features of a business organization-enterprise, and the ownership structure can function most effectively on a corporate model in the form of a joint stock company. Conclusions on the incapacity of the current model of ownership and management of an apartment building, the need to improve the model of condominiums as a subject of management of the object - a condominium; formation of a new segment of corporate-owned houses in joint households are formulated.